Reconstruction of the arts sector : roadmap for a sustainable future - (:unkn) unknown (Taideyliopisto, 2022)
This report has been conducted as part of the Arts Sector Reconstruction Programme launched by the University of the Arts Helsinki. The main purpose of the review work was to produce information on how to build a sustainable future for the arts sector for the use of the “Future of the Cultural Sector” working group set by Minister Antti Kurvinen. The goal of the study was to identify transition paths that will lead the arts sector to a sustainable future by reflecting on sustainability challenges and possible solutions, especially from the perspective of the independent arts sector. The premise of the review was to focus primarily on finding solutions that would not depend on the growth of public funding for the arts. The review work was carried out between autumn 2021 and spring 2022. Material was gathered through 20 interviews, 157 responses to an online questionnaire and two workshops. As part of the review work, the Center for Cultural Policy Research Cupore compiled a summary of research results and statistics presenting the effects of the pandemic as well as the central support methods that were applied in Finland and in European benchmarks. Background information was gathered from notes and material that were compiled during Kulta ry’s “Future Tour” around Finland as well as from relevant research results, reports and strategy documents. Findings from the material highlight the fact that the structural problems and deficiencies in the field are even more significant than the acute crisis caused by the pandemic. However, the arts and cultural sector has been hit hard by the COVID-19 pandemic and the consequent restrictions. The research material shows a strong experience of injustice and lack of appreciation and a weakened trust in public authorities. The analysis of sustainability challenges was followed by the outlining of four transition paths that would lead to a more sustainable future: 1) sustainable earning methods, 2) art as part of society, 3) renewal through unprecedented events and 4) post-pandemic measures. Central capabilities that are needed for reaching the goals under each path are discussed in the report.
Keywords: kulttuuripolitiikka; rahoitus; taideala; taidekorkeakoulut; kestävyys; kyvykkyys; jälleenrakentaminen; tulevaisuus